On religion and memory (Fordham University Press, 2013)
This volume explores the status of temporality in a selection of sources ranging from Augustine to Virginia Woolf. The volume's essays, expressed by a number of Christian religious thinkers, take up Augustine's paradox of time: how to account for the continuity of history and the certitude of memory if the indivisible 'now' of time cuts off any extension?